PENERAPAN PENDEKATAN MANPOWER PLANNING DALAM PERENCANAAN PEMBIAYAAN PENDIDIKAN UNTUK MENGATASI PENGANGGURAN SMK - Marwani, Ana; Anita Nadzifah; Patto Prawansyah; Nurkholis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the problems of unemployment of educated workers which are in the public spotlight. A policy is needed that can increase the relevance of Vocational High Schools (SMK) to the needs of the world of work, the business world and the industrial world. This research uses a qualitative research method with a case study research approach which aims to study intensively the background of the unemployment problem and how manpower planning implementation policies can be a solution to the unemployment problem. The results of this research will provide a broad and in-depth picture of the application of manpower planning, namely that with manpower planning Vocational Education can find out what competencies (skills) are most needed by the world of work and what competencies are most needed by the world of work.